Implementation of Obstruction of Justice in News Reporting Cases (A Case Study of the Suspect Designation of Tian Bahtiar in Jak TV Coverage) - Dewi Fiandika Sari; Ahmad Suryono (SS&H: Studies in Social Sciences and Humanities, 2026)
This study examines the application of obstruction of justice in the context of media reporting, focusing on the case of the suspect designation of Tian Bahtiar in Jak TV coverage. The issue arises from the intersection between law enforcement interests and press freedom, particularly when journalistic activities are alleged to interfere with legal processes. This research employs a normative juridical method using statutory and conceptual approaches to analyze whether the elements of obstruction of justice, as regulated under Article 21 of the Anti-Corruption Law, are fulfilled. The findings indicate that although the element of “every person” is met, other essential elements such as intentional conduct, acts of preventing, obstructing, or thwarting the legal process, and both direct or indirect interference are not sufficiently proven. The reporting activities carried out were found to fall within the scope of journalistic functions and did not demonstrate a clear causal relationship with the disruption of law enforcement processes. Therefore, the application of obstruction of justice in this case is considered legally inappropriate. This study highlights the importance of maintaining a balance between effective law enforcement and the protection of press freedom in a democratic legal system.